2021
DOI: 10.48550/arxiv.2112.11600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical Modelling of Exoplanet Transit Specroscopy with Dimensional Analysis and Symbolic Regression

Abstract: The physical characteristics and atmospheric chemical composition of newly discovered exoplanets are often inferred from their transit spectra which are obtained from complex numerical models of radiative transfer. Alternatively, simple analytical expressions provide insightful physical intuition into the relevant atmospheric processes. The deep learning revolution has opened the door for deriving such analytical results directly with a computer algorithm fitting to the data. As a proof of concept, we successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…The analytical formulas typically rely on simplifying assumptions and approximations,.e.g, spherical symmetry, isothermal atmosphere, isobaric approximation, constant specific gravity, etc. Nevertheless, these theoretical results agree well with the numerical forward models and allow for better understanding of the underlying physics and of the intrinsic parameter degeneracies present in the problem (Griffith 2014;Heng & Kitzmann 2017;Welbanks & Madhusudhan 2019;Matchev et al 2021).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The analytical formulas typically rely on simplifying assumptions and approximations,.e.g, spherical symmetry, isothermal atmosphere, isobaric approximation, constant specific gravity, etc. Nevertheless, these theoretical results agree well with the numerical forward models and allow for better understanding of the underlying physics and of the intrinsic parameter degeneracies present in the problem (Griffith 2014;Heng & Kitzmann 2017;Welbanks & Madhusudhan 2019;Matchev et al 2021).…”
Section: Introductionsupporting
confidence: 72%
“…The first simplification arises due to standard dimensional analysis (Langhaar 1951;Barenblatt 1996). Matchev et al (2021) showed that, again without any loss of generality, the analytical expression behind the forward model ( 5) must be of the form…”
Section: Analytical Modelsmentioning
confidence: 99%
“…This implies that the five degrees of freedom are reduced effectively to only two: the temperature T and the total opacity 𝜅. One can reach similar conclusions on the basis of dimensional analysis as in Matchev et al (2021). As an illustration, in Figure 2 we show scatter plots of one representative feature (𝑀 (𝜆 1 ) for 𝜆 1 = 0.867 𝜇m) versus the two relevant degrees of freedom: the temperature 𝑇 (left panel) and a convenient naive proxy for the total atmospheric opacity in eq.…”
Section: The Synthetic Benchmark Data Setsupporting
confidence: 58%
“…2014; Heng & Kitzmann 2017;Welbanks & Madhusudhan 2019;Matchev et al 2021); transparent and reproducible results.…”
Section: Synthetic Datamentioning
confidence: 86%
See 1 more Smart Citation